Media and the War on Terrorism - Hess, Stephen (Ed.); Kalb,Marvin (Ed.) (New York, 2003)
These candid conversations capture the difficulties of reporting during crisis and war, particularly the tension between government and the press. the participants include distinguished journalists-- American and foreign, print and broadcast and prominent public officicials, past and present. They illuminate the struggel to balance freedom of the press with the need to protect sensitive information in the national insterest. About Author : Stephen Hess is a senior fellow at the Brookings institution. He is the author of many books, including the washington reporters and organizing the presidency. Contents : Foreword Part I: The Media and the Government: World War II to the end of the Twentieth century Part II: War in Afghanistan The early stages The Journalists dilemma: Three stories Part 4: Reporting from the field three sites Part 5: From different perspective Part 6: 9/11 and beyond index
Keywords: Terrorism